Improving Students’ Reading Comprehension through Cooperative Learning Strategies Using Numbered Heads Together - Nelli Nelli; Elysa Hartati ((JELE) Journal Of English Language and Education, 2018)
This research aimed at improving students reading comprehension through cooperative learning strategies using numbered heads together in MTs Ma’arif 2 Muntilan. This was classroom action research with 3 cycles. There were 4 steps in conducting the research; (1) Planning; (2) Acting; (3) Observing; (4) Reflecting. This research involved 27 students of eight graders. The instruments used in this research were observation, interview, test (pre-test and post- test), field-notes, questionnaire, and documentation. It was found that the students’ average score in pre-test was 46, the first post-test was 59. The second post-test was 81 and the third post-test was 94. It meant that the post-test was higher than pre-test. Besides, the students also had been well interested during the learning process in each cycle. In conclusion, the findings of this research showed that through CL strategies using NHT could improve the students’ reading comprehension. Hence, it is recommended for the further researcher to use NHT as an alternative strategy in improving the students’ reading comprehension.